Concept paper: why managing universities like entrepreneurs will solve financial problems in institutions of higher learning - Zaludin, Zairil Azhar (Human Resource Management Academic Research Society, 2019)
All over the world today, university managers and administrators complain about the lack of funding support from the government for their establishment. In the UK, a few universities are already at risk of being closed down due to financial difficulties. In Malaysia, the budget allocated for public universities has also been slashed significantly causing a lot of discomfort among university administrators. Ironically, universities by default are full of potential wealth from the one source they are supposed to have abundance –their intellects. While some universities suffer, other successful universities prosper by focusing on capitalizing on their biggest assets –their highly qualified staff and the commercialization of their inventions and innovation that are produced from their own minds and hard work. Intellectual properties and other lucrative spin-off become their major source of income. Looking closer, the way governments want their public universities to be run appear to be more and more synonymous to the way a small startup company should be run. Governments seem to want these universities to be self-sustained, well managed, independent from any chronic financial support, to name a few. Governments appear to be hoping that universities have enough intelligence to be financially independent. However, the message did not appear to be transmitted or understood well enough. Instead, wasteful projects, mismanagement of institutions, incompetent leadership and financial abuse are common problems in universities today. This paper proposes a concept that is simple to adopt. Run universities like a good entrepreneur. By focusing on the institution's biggest assets –their staff, knowing the institution strength, accepting their own limitations and appreciating their resources, universities should be able to be self-sustained like a good successful company. Governments too, must choose administrators with successful entrepreneur experience and mindset thus, less from irrelevant overly glorified academic background. And like all entrepreneurs who value their staff, universities should capitalize and value better their biggest asset of all –their highly qualified staff.